The survival of Odebrecht in Brazil after an international construction bribery scandal - Osland, Asbjørn (London : SAGE Publications: SAGE Business Cases Originals, 2020)
Odebrecht SA of Brazil is a holding company with assorted subsidiaries. Investigators revealed that many contracts Odebrecht received for construction projects resulted from bribery. Authorities in Brazil, Switzerland, and the United States investigated and successfully prosecuted the case. Between 2001 and 2016, Odebrecht and its co-conspirators paid roughly USD 788 million in bribes pertaining to over 100 projects in 12 countries, mainly in Latin America but also Angola and Mozambique in Africa. Odebrecht must now change internally as it withstands economic pressure from fines and lost business and entering bankruptcy.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Odebrecht SA -- Case studies; Construction industry -- Corrupt practices -- Brazil -- Case studies